Is driving without a valid license associated with an increased risk of causing a road crash?. (January 2021) - Martín-delosReyes, Luis Miguel; Martínez-Ruiz, Virginia; Rivera-Izquierdo, Mario; Jiménez-Mejías, Eladio; Lardelli-Claret, Pablo
Highlights: The association between driving without a valid license and a higher risk of road crash has been previously reported. Concerns remain about the adjusted strength of the association for each type of infraction, and the proportion explained by other factors. All infractions were related to a higher risk of causing a crash, particularly 'suspended license' and 'never having held a license'. The proportion of this relationship that can be explained by other risk factors -especially driving behaviors- was high. Our results support the need to identify and control these drivers. Abstract: The aim of this study was to estimate the association between each cause of driving without a valid license (DWVL) and the risk of causing a road crash, considering driver, vehicle and environmental factors. A case-control study based on data from the Spanish Register of Road Accidents with Victims was carried out between 2014 and 2017. Cases included 28, 620 drivers of moving private cars, vans and off-road vehicles involved in single crashes plus 50, 100 drivers deemed responsible for clean collisions (i.e. those in which only one driver was labeled as responsible). In accordance with the quasi-induce exposure approach, drivers not responsible for clean collisions comprised the control group (N = 51, 656). Logistic and multinomial regression models were used to estimate crude and adjusted Odds Ratios or Relative Risk Ratios between each reason for DWVL and the risk of being a case of all, single and multi-vehicle collisions. A significant association was found between all reasons for DWVL and the risk of causing a road crash. This association was particularly high for drivers with a suspended license and drivers who had never obtained a license. In these subgroups of drivers, the proportion of the relationship explained by high-risk driving behaviors is high. Our results support the need for applying continued strategies to identify and control these subgroups of drivers.